THE EFFECT OF WORK MOTIVATION ON TEACHER PERFORMANCE AT PRIVATE VOCATIONAL HIGH SCHOOLS IN BIAK NUMFOR DISTRICT, PAPUA - Mahdi; Yulius Mataputun; Ida M. Hutabarat (JF Publisher, 2023)
Teacher work motivation is a very important factor in affecting teacher performance to achieve educational goals. Quality teacher performance can improve the quality of educational institutions and vice versa. Therefore, this research was conducted to analyze the effect of work motivation on teacher performance in selected private vocational high schools in Biak Numfor district, Papua. This research used quantitative approach with correlational type. The population in this research was teachers at four private vocational high schools in Biak Numfor district, Papua. The sampling technique used saturated samples. The research object consisted of 115 teachers who work in four private vocational schools in Biak Numfor district, Papua. This research instrument is a closed questionnaire and several supporting documents. The data analysis technique used simple linear regression. The research findings identified that there is a significant positive effect of work motivation on teacher performance in private vocational high schools in Biak Numfor district, Papua, with 37.1% indicating that it is in the low category. Furthermore, according to the research results, teachers perform better when they are more motivated at their work.